Tribological behaviour of hot extruded Al–Cu–Mg–Ag alloy reinforced by TiB2 particles. Issue 8 (24th May 2019) - Saxena, Abhinav; Indriyati, Martha; Rajveer,; Biswas, Prasenjit; Kotadia, Hiren R.; Das, Sanjeev
ABSTRACT: In the present investigation, tribological behaviour of the hot extruded Al–Cu–Mg–Ag (matrix) alloy and the effect of Ti and TiB2 addition in matrix alloy have been studied. Hot extrusion was introduced to eliminate cast defects like porosity, voids and micro cracks. Addition of Ti and TiB2 particles increased the hardness of the matrix by grain refinement and dispersion hardening, respectively. It has been observed that the increase in hardness had significantly improved the wear resistance of the material. Detail study of the wear surfaces and debris were carried out to understand the wear mechanism of the samples. It revealed a complex mechanism of micro-cutting, plastic deformation, abrasion and delamination of the wear samples.